Differences in Halothane and Isofluran Anesthesia on Hemodynamic Status - Alva Cherry mustamu; Difran Nobel Bistara; Susanti (Universitas Nahdlatul Ulama Surabaya, 2023)
Halothane and Isoflurane are two frequent inhalation agents used as maintenance anesthesia during surgery. After experiencing anesthesia, many patients experience decreased hemodynamic status as pressure blood, respiration, and pulse. Because that study this expected could determine proper anesthesia for use.Evaluates differences in hemodynamic status post-anesthesia consequence use of halothane and isoflurane.This is a study with quasi pre-post design experiment with a control group design. The samplestudy is all patients undergoing Installation Surgery at Sele Be Solu Hospital, Sorong City, which uses the general anesthesia technique with inhalation of halothane or isofluranefor as many as 21 people. Instrument study use sheet observation to measure pressure, blood, respiration, and pulse During surgery.The Wilcoxon test obtained a score of 0.157 on the pressure blood respondent after getting anesthesia halothane and respondents after getting anesthesia isoflurane, i.e., 0.007.Mann Whitney test shows changes in blood pressure, pulse, and respiration in anesthetized respondents who used halothane and isoflurane score significance of 0.784, 0.576, and 0.307.There is a difference in blood pressure at first and end anesthesia use of isoflurane. No, there is a difference in frequency pulse, initial pulse, and respiration anesthesia, and end anesthesia usesisoflurane. Nothere is a difference in pressure blood, pulse, and respiration at the beginning and end anesthesia useshalothane. There is no difference in blood pressure, pulse, and respiration after general anesthesia uses isoflurane and halothane